2019
DOI: 10.1016/j.jaip.2018.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Quality of Life in a Multicenter, Randomized, Placebo-Controlled Trial of Low-Dose Peanut Oral Immunotherapy in Children with Peanut Allergy

Abstract: Efficacy, safety and quality of life in a multi-center, randomized, placebo-controlled trial on low-dose peanut oral immunotherapy in peanut allergic children

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
191
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(204 citation statements)
references
References 36 publications
5
191
1
7
Order By: Relevance
“…6 Such studies have demonstrated that immunotherapy can successfully desensitize patients to peanut. [7][8][9][10][11][12][13][14][15][16] However, it is not clear whether longterm tolerance is sustainable without continuous peanut dosing after active therapy.…”
mentioning
confidence: 99%
“…6 Such studies have demonstrated that immunotherapy can successfully desensitize patients to peanut. [7][8][9][10][11][12][13][14][15][16] However, it is not clear whether longterm tolerance is sustainable without continuous peanut dosing after active therapy.…”
mentioning
confidence: 99%
“…Caregivers should be included in shared decision-making about, whether to initiate OIT early for these foods and based on individual prognosis, considering that OIT is well tolerated and has high efficacy in this age group This recommendation is based on the principle of equity in eligibility as well as proportionality between risks and benefits, considering patient's goals and perspectives For desensitization, it is supported by a large amount of consistent clinical evidence. Many OIT studies (RCTs [34,41,43,47,49,59,60] as well as large clinical practice case series [32,33,40,54]) enrolled children starting from the age of 4 or 5 years; some have started enrolment from age three [29,61] or one [46,62]. In addition, there is a moderate amount of consistent evidence specifically for this age group from one RCT of milk OIT (unclear risk of bias-Cochrane) [63], one large (N = 270) prospective, multi-center case series in clinical practice of peanut OIT (low risk of bias-IHE tool) [30] and one small (N = 37) prospective, uncontrolled clinical trial of peanut OIT [58].…”
Section: Ethical Imperative Data or Other Considerations In Support mentioning
confidence: 99%
“…For desensitization, it is supported by a large amount of consistent clinical evidence. Most of the evidence for desensitization stems from studies that enrolled children and adolescents with median/mean ages in the range of 6 to 12 years (RCTs [31, 34, 39, 41, 43, 46, 49, 59-61, 64, 65] and large clinical practice case series [32,33,40,54]) In nine RCTs [34,39,41,43,44,47,59,61,64] and five large clinical practice case series [29,32,33,40,54], the upper age limit for enrolment was 16 years or older (up to 27 years [32]). This is coherent with data from consultations.…”
Section: Oit Is Indicated For School-age Children and Adolescentsmentioning
confidence: 99%
“…The major issues in treating food allergy by immunotherapy are safety, the low rate of tolerance induction, a high rate of side effects and dropouts, a lack of understanding of the optimal dose and time of treatment, and the existence of only few, suboptimal biomarkers that predict treatment response and how to perform multifood OIT . These limitations are addressed in numerous treatment approaches: (a) peptide immunotherapy targeting the T‐cell compartment and lacking IgE cross‐linking; (b) hypoallergenic variants of allergens or extracts by chemical or thermal modification or mutations which combine reduced desensitization with a minimally altered T‐cell epitope diversity; (c) the usage of immunomodulatory substances and/or particles; (d) the addition of prebiotics and/or probiotics; (e) the application of biologics either alone or as adjuvants of OIT; (g) very low dose OIT; and (h) sublingual OIT.…”
Section: Unmet Needs and Future Research Areas In Treatment Of Allergmentioning
confidence: 99%
“…155 The major issues in treating food allergy by immunotherapy are safety, the low rate of tolerance induction, 155 a high rate of side effects and dropouts, 153 a lack of understanding of the optimal dose and time of treatment, and the existence of only few, suboptimal biomarkers that predict treatment response and how to perform multifood OIT. 13,157,158 addition of prebiotics and/or probiotics 76,166 ; (e) the application of biologics either alone 167,168 or as adjuvants of OIT 169,170 ; (g) very low dose OIT 171,172 ; and (h) sublingual OIT.…”
Section: How To Treat Food Allergy In the Future: New Developments mentioning
confidence: 99%